Geographic Information Systems and Location of a Sanitary Landfill in Cerro de Pasco - Estacio Vidal, Jesús Manuel (2021)
This study arises as a result of the problem in the location of solid waste final disposal infrastructures (Landfill) where various analysis criteria are taken into consideration following the provisions of DL Regulation N° 1278 Comprehensive Waste Management Law Solid DS N° 014-2017-MINAM. The optimal location analysis was carried out using the Multicriteria Spatial Analysis (AEMC) processes as well as the hierarchical analysis process (AHP) applying it in a Geographic Information System (ArcGis). The purpose of the investigation was to locate the appropriate areas for the final disposal of solid waste in the city of Cerro de Pasco. The results present the consideration of 6 alternative locations for the sanitary landfill, all of them between 3 and 4.13 km away from the city, under physical, environmental, socioeconomic and legal criteria. It is concluded that geographic information systems, multi-criteria spatial analysis and hierarchical analysis are appropriate for solving location problems.